Exploring the Role of Artificial Intelligence in Shaping Teacher Identity and Digital Pedagogy in English Language Education - Zhang, Jianfang (European Journal of Social Science Education and Research, 2025)
In the era of the digital economy, increasing digital literacy has emerged as one of China’s key policies, which has led to the crucial goal of English education to develop digital talents. In Zhejiang, 190 higher English teachers participated in an online survey on digital literacy. Data research revealed that English teachers had a comparatively high self-score for digital literacy. Digital literacy’s four dimensions are, the Awareness in digital, Thinking Computationally, Innovation and Learning in Digital, Digital Protection and Transparency. The IFSO-DAdaBoost method presents a comprehensive skill evaluation, enhances skill extraction accuracy, facilitates intelligent learning, and improves data representation. When compared to the current method, the proposed IFSO-DAdaBoost strategy shows a significant increase in accuracy. The strategy achieves 99.2% accuracy, 98.6% precision, 99.0% recall, and a 98.9% F1 score. The error performance decreased by RMSE of 0.3524, MAE of 0.1832, and MAPE of 4.24 based on the error measurements.